(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A smart city is a city where data and technology are used to better the lives of its residents. Oneof the most important factors in the evolution of smart cities is the advent of the Internet of Things(IoT). The Internet of Things (IoT) enables cities to better allocate their resources, save expenses, andenhance the quality of services they provide to their residents by providing a centralized hub forcollecting, analyzing, and acting on data. The Internet of Things allows for the collection of data from awide variety of sources, the real-time monitoring of infrastructure and services, the use of predictiveanalytics to foresee potential problems, and the improvement of citizen services through the provision oftimely information and feedback. The Internet of Things is essential to the growth of smart cities becauseit improves the effectiveness of municipal services and infrastructure while also raising the standard ofliving for the local populace.